Dakriosistitis - Muhamad Zaidan Algifari; Putu Ristyaning Ayu Sangging; Rani Himayani (CV. Jasa Sukses Abadi, 2023)
Dacryocystitis is characterized by inflammation of the nasolacrimal sac. This is due to obstruction within the nasolacrimal duct and stagnation of tears in the lacrimal sac. Obstruction that occurs in the nasolacrimal duct can cause secondary infection in the form of dacryocystitis. Obstruction that occurs at an early age is caused by the nasolacrimal membrane not opening, whereas in adults it is due to pressure on the nasolacrimal duct. The most common organisms found in dacryocystitis are staphylococcal species (mostly S. aureus, S. pneumoniae, and S. epidermidis). Symptoms found in dacryocystitis are redness, swelling, and pain above the lacrimal sac, especially just below the anatomical boundary of the medial canthal ligament. Conservative therapy is carried out by applying warm compresses 3 times a day, given analgesics and oral antibiotic therapy. The most common surgical procedure for dacryocystitis is Dacryocystorhinostomy (DCR). DCR has been reported to be over 93% to 97% successful. Complications that can occur as a result of not being handled properly are presptal cellulitis or orbital cellulitis. In general, the prognosis for dacryocystitis is good.